Long-range-projecting GABAergic neurons modulate inhibition in hippocampus and entorhinal cortex - Melzer, Sarah; Michael, Magdalena; Caputi, Antonio; Eliava, Marina; Fuchs, Elke C.; Monyer, Hannah (Science, 2012)
The hippocampus and entorhinal cortex play a pivotal role in spatial learning and memory. The two forebrain regions are highly interconnected via excitatory pathways. Using optogenetic tools, we identified and characterized long-range γ-aminobutyric acid-releasing (GABAergic) neurons that provide a bidirectional hippocampal-entorhinal inhibitory connectivity and preferentially target GABAergic interneurons. Activation of long-range GABAergic axons enhances sub- and suprathreshold rhythmic theta activity of postsynaptic neurons in the target areas.